Schiller and Music - Longyear, Rey M. (1966)
In this first definitive study of Friedrich Schillers relationship to music, R. M. Longyear discusses Schillers personal, literary, and philosophical utilization of music as well as the influence of Schillers works on composers from 1782 through the 1960s